Targeted Approaches to Inhibit Sialylation of Multiple Myeloma in the Bone Marrow Microenvironment - Natoni, Alessandro; Bohara, Raghvendra; Pandit, Abhay; O'Dwyer, Michael (Frontiers in Bioengineering and Biotechnology, 2019)
Aberrant glycosylation modulates different aspects of tumor biology and it has long been recognised as a hallmark of cancer. Among the different forms of glycosylation, sialylation, the addition of sialic acid to underlying oligosaccharides, is often dysregulated in cancer. Increased expression of sialylated glycans has been observed in many types of cancer, including multiple myeloma, and often correlates with aggressive metastatic behaviour. Myeloma, a cancer of plasma cells, develops in the bone marrow and colonises multiple sites of the skeleton including the skull. In myeloma, the bone marrow represents an essential niche where the malignant cells are nurtured by the microenvironment and protected from chemotherapy. Here, we discuss the role of hypersialylation in the metastatic process focusing on multiple myeloma. In particular, we examine how increased sialylation modulates homing of malignant plasma cells into the bone marrow by regulating the activity of molecules important in bone marrow cellular trafficking including selectins and integrins. We also propose that inhibiting sialylation may represent a new therapeutic strategy to overcome bone marrow-mediated chemotherapy resistance and describe different targeted approaches to specifically deliver sialylation inhibitors to the bone marrow microenvironment.